Insectos visitantes florales de Phytelephas macrocarpa (Arecaceae), una palma dioica al noroeste de la Amazonia peruana - Ramírez Castillo, Sandro A. (2024)
Phytelephas macrocarpa is a dioecious palm that lacks studies on the entomofauna that visit its flowers in western Amazonia. In this study we identified the insect visitors and their interaction with the inflorescences of P. macrocarpa in two localities in northwestern Peruvian Amazonia. Additionally, the richness and abundance of these insects was determined. For this purpose, six inflorescences were collected per locality (three male and three female). During field trips, the interactions of the insects on the inflorescences were observed. A total of 28 106 insects distributed in 27 species were recorded, where Amazoncharis sp., Aleochara sp. and Anchylorhynchus